Effects and Mechanism of Action of a Tribulus terrestris Extract on Penile Erection - Do, Jungmo (The Korean Urological Association, 2013)
PURPOSE: Tribulus terrestris has been used as an aphrodisiac. However, little is known about the effects and mechanism of action of T. terrestris on penile erection. Therefore, the effect of a T. terrestris extract and the mechanism of action of the extract on relaxation of the corpus cavernosum (CC) were investigated. The erectogenic effects of an oral preparation of the extract were also assessed. MATERIALS AND METHODS: The relaxation effects and mechanism of action of the T. terrestris extract on rabbit CC were investigated in an organ bath. The intracavernous pressure (ICP) was calculated after oral administration of the extract for 1 month to evaluate whether the relaxation response of the CC shown in the organ bath occurred in vivo. Additionally, cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) were measured in the CC by immunoassay. Smooth muscle relaxation was expressed as the percentage decrease in precontraction induced by phenylephrine. The ICP was also assessed in rats after oral administration of the extract for 1 month, and changes in concentrations of cGMP and cAMP were monitored. RESULTS: Concentration-dependent relaxation effects of the extract on the CC were detected in the organ bath study. Relaxation of the CC by the T. terrestris extract was inhibited in both an endothelium-removed group and an L-arginen methyl ester pretreatment group. The ICP measured after oral administration of the T. terrestris extract for 1 month was higher than that measured in the control group, and a significant increase in cAMP was observed in the T. terrestris extract group. CONCLUSIONS: The T. terrestris extract induced concentration-dependent relaxation of the CC in an organ bath. The mechanism included a reaction involving the nitric oxide/nitric oxide synthase pathway and endothelium of the CC. Moreover, in an in vivo study, the T. terrestris extract showed a significant concentration-dependent increase in ICP. Accordingly, the T. terrestris extract may improve erectile function.